2021
DOI: 10.1111/fme.12514
|View full text |Cite
|
Sign up to set email alerts
|

Data‐poor stock assessment of fish stocks co‐exploited by commercial and recreational fisheries: Applications to pike Esox lucius in the western Baltic Sea

Abstract: The management of mixed-use fisheries, that is fisheries that are co-exploited by commercial and recreational fishers, poses many challenges. For instance, commercial and recreational fisheries often have different management objectives (Ahrens et al., 2020;Arlinghaus et al., 2019), and the differences in goals and behaviours increase with the diversity of stakeholders (Mardle et al., 2004;Pascoe et al., 2009). The sustainable management of mixed-use fisheries requires monitoring and managing both its commerci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…In areas with co-exploitation of stocks by commercial and recreational fisheries (as in the lagoon fishery around Rügen), both biomass and catch rate/trophy fish size related objectives are jointly relevant (Gemert et al, 2022), and compromises have to be reached between competing objectives (Ahrens et al, 2020). Using an integrated multi-objective utility function, we found that scale-informed models would favor a higher optimal minimum-length limit (around 80 cm) compared to models informed by otoliths or corroborated age(around 75 cm).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In areas with co-exploitation of stocks by commercial and recreational fisheries (as in the lagoon fishery around Rügen), both biomass and catch rate/trophy fish size related objectives are jointly relevant (Gemert et al, 2022), and compromises have to be reached between competing objectives (Ahrens et al, 2020). Using an integrated multi-objective utility function, we found that scale-informed models would favor a higher optimal minimum-length limit (around 80 cm) compared to models informed by otoliths or corroborated age(around 75 cm).…”
Section: Discussionmentioning
confidence: 99%
“…The current minimum-length limit for pike in the Rügen lagoons of 50 cm was used as default for assessing fisheries reference points. To mimic impacts of the growth models on future policies, we varied the minimum-length limit as a common harvest regulation measure between 50 and 100 cm in steps of 1 cm among model simulations with F fixed at 0.2 year -1 , representing the current fishing pressure estimated from stock assessment (Gemert et al, 2022). The one minimum-length limit maximizing the log-utility function composed of the five objectives mentioned above was defined as optimal and could be interpreted as the best compromise among multiple management objectives as in Ahrens et al (2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…declining or increasing) rather than absolute population status. Leveraging digital fisheries data can be useful for data‐poor fisheries where assessment and management are constrained (Arlinghaus & Krause, 2013; Pilling et al, 2009), or to supplement traditional stock assessments that may not have historical context to draw on (van Gemert et al, 2022). Analog analogues of digital fisheries data illustrate how access to historic records can provide information to fisheries management where digital fisheries data are too new to provide suitable examples.…”
Section: Recreational Fisheries Management Questions and Their Potent...mentioning
confidence: 99%
“…cal context to draw on(van Gemert et al, 2022). Analog analogues of digital fisheries data illustrate how access to historic records can provide information to fisheries management where digital fisheries data are too new to provide suitable examples.…”
mentioning
confidence: 99%